Suicide risk among adolescents in Sarawak, Malaysia: prevalence and determining factors. - Ying, Wong Khung; Md Mizanur, Rahman; Andrew, Kiyu (De Gruyter, 2024)
Objectives Adolescent suicide is a significant global public health concern. Although numerous studies have investigated factors that influence the risk of suicide among adolescents around the world, limited data are available in the Malaysian context, especially among the diverse ethnic communities of Sarawak. This study aimed to determine the factors associated with the risk of suicide among adolescents in Sarawak, Malaysia. Methods A community-based cross-sectional study was conducted among 1,344 adolescents in Sarawak using face-to-face interviews. Hierarchical binary logistic regression analysis was performed to identify factors that determine the risk of suicide among adolescents.